2014
DOI: 10.1111/ene.12470
|View full text |Cite
|
Sign up to set email alerts
|

Subjective memory complaints, depressive symptoms and cognition in Parkinson's disease patients

Abstract: Approximately 15% of PD patients seeking help in a movement disorder clinic report significant SMCs, with an increasing degree from cognitively healthy PD to PD-MCI. Significant DSs increase SMCs across all cognitive status groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 26 publications
6
97
3
Order By: Relevance
“…Among the components of NMS, depression has been demonstrated to influence cognitive function [6]. One study reported premorbid depression to adversely affect improvement of motor symptoms after deep brain stimulation for PD [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among the components of NMS, depression has been demonstrated to influence cognitive function [6]. One study reported premorbid depression to adversely affect improvement of motor symptoms after deep brain stimulation for PD [7].…”
Section: Introductionmentioning
confidence: 99%
“…7 In another study using a self-report questionnaire, 16% of patients with PD subjectively reported memory problems, which rose to 31% if memory impairment was detectable on neuropsychological testing. 8 Inferior memory test results correlated with subjective memory complaint, suggesting that patients with PD had some level of awareness of their memory problems; however, no caregiver ratings of memory function were reported. Using the new MDS Task Force criteria, we examined whether patient and caregiver ratings differed between patients who were diagnosed with and without PD-MCI, and we investigated the relationship between patient and caregiver ratings of memory change against objective neuropsychological test performance.…”
mentioning
confidence: 90%
“…In addition, patients with PD‐MCI who were identified with poor day‐to‐day memory function as per caregiver report also showed reduced performance on neuropsychological tests of processing speed, learning and memory, executive function, and language . In another study using a self‐report questionnaire, 16% of patients with PD subjectively reported memory problems, which rose to 31% if memory impairment was detectable on neuropsychological testing . Inferior memory test results correlated with subjective memory complaint, suggesting that patients with PD had some level of awareness of their memory problems; however, no caregiver ratings of memory function were reported.…”
mentioning
confidence: 99%
“…25,26 Lower prevalence rates are reported when diagnostic status is based on clinical interview and Diagnostic and Statistical Manual of Mental Disorders (DSM) diagnostic criteria are applied, whereas higher prevalence is reported in studies utilizing self-report scales and empirically established cutoffs to obtain depression rate estimates. 25 The prevalence of PD patients meeting DSM-5 criteria for a major depressive disorder is estimated to be 17%; minor depression (generally characterized as clinically significant depressive symptoms that do not meet DSM criteria for major depression or dysthymia) 27 is estimated to occur in 22% of patients, and dysthymia, or persistent low mood for a period of 2 years, is estimated to occur in 13% of patients.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%